The ethical relevance of the unconscious - Farisco, Michele (Philos Ethics Humanit Med, 2017)
BACKGROUND: Ethical analyses of disorders of consciousness traditionally focus on residual awareness. Going one step further, this paper explores the potential ethical relevance of the unawareness retained by patients with disorders of consciousness, focusing specifically on the ethical implications of the description of the unconscious provided by recent scientific research. METHODS: A conceptual methodology is used, based on the review and analysis of relevant scientific literature on the unconscious and the logical argumentation in favour of the ethical conclusions. RESULTS: Two conditions (experiential wellbeing and having interests) that are generally considered critical components in the ethical discussion of patients with disorders of consciousness might arguably be both conscious and unconscious. CONCLUSIONS: The unconscious, as well as consciousness, should be taken into account in the ethical discussions of patients with disorders of consciousness.